Rapid utilisation of telehealth services for specialist paediatric general surgery outpatient clinics in response to COVID-19 - David Cruise; Haydn Cruise; Michael Collin; Parshotam Gera (SpringerOpen, 2022)
Abstract Background The COVID-19 pandemic is highly infectious and prompted, amongst other changes, strict social distancing requirements for medical practitioners in Western Australia. Despite significant previous research into telehealth, uptake had been limited beyond servicing rural patients, in spite of numerous purported benefits. Results Rapid adoption of telehealth for a majority of outpatient appointments was instituted in the sole tertiary paediatric general surgery with high overall success rates - a satisfactory outcome being achieved without requiring an in-person appointment (97.1% for telephone consults, 93.8% for videoconferencing) during the initial COVID-19 crisis from April to June 2020. Success of appointments was lowest for new referrals for undescended testicles at 81.3%. Operations booked through telehealth consultations were only altered in 1 case (5%), and this was not significantly different to in-person bookings (p > 0.05). No cases of COVID-19 were incurred by the surgical team or patients during the study period. Conclusions We found that with existing technology and minimal training, paediatric surgical consultations were able to be performed via telehealth with high success, high accuracy, and without significant adverse outcomes.